Eco-evolutionary dynamics - Hendry, A. P. (Andrew P.) (Princeton University Press, 2017)
In recent years, scientists have realized that evolution can occur on timescales much shorter than the "long lapse of ages" emphasized by Darwin--in fact, evolutionary change is occurring all around us all the time. This book provides an authoritative and accessible introduction to eco-evolutionary dynamics, a cutting-edge new field that seeks to unify evolution and ecology into a common conceptual framework focusing on rapid and dynamic environmental and evolutionary change. Andrew Hendry covers key aspects of evolution, ecology, and their interactions. Topics range from natural selection, adaptive divergence, ecological speciation, and gene flow to population and community dynamics, ecosystem function, plasticity, and genomics. Hendry evaluates conceptual and methodological approaches, and draws on empirical data from natural populations--including those in human-disturbed environments--to tackle a number of classic and emerging research questions. He also discusses exciting new directions for future research at the intersection of ecology and evolution. An invaluable guide for students and researchers alike, Eco-evolutionary Dynamics reveals how evolution and ecology interact strongly on short timescales to shape the world we see around us. -- Provided by publisher.